Internet Search mechanisms and distortions of the semantic space: The Scientific challenges facing the “googles” - Linhares, Alexandre; Afonso, Carla Winter (PRISMA.COM, 2007)
Ever since the launch of Altavista, internet search engines have become a multi-billion dollar industry, with fierce competition between Google and the three major competitors. One of the challenges involved is to rank search results in a way that places the most meaningful results at the top. In order to do this, the algorithms involved must try to grasp the actual meaning, the semantics, embedded in a search query. In this paper we discuss a problem we call "distortions of semantic space". Distortions of semantic space occur regularly in people's texts, writing styles, labeling of images, etc. We present a number of examples of distortions of semantic space, and analyze the problem. We also comment on new computational architectures that have tried to handle this problem, albeit the state of the art still remains far from the needed.